PROBLEMS AND STRATEGY OF CREATING A CHATBOT «PSYCHOLOGY» - Mintser, O.P.; Lukyanov, Ye. Yu. (Medical Informatics and Engineering, 2025)
Background. This paper addresses the use of chatbots in psychology. The study tracks the dynam- ics of task changes when employing chatbots, the directions of their use, and the risks associated with implementing the technology. The aim of the research is to substantiate the specific strategies for developing chatbots in the field of psychology. Materials and methods. The study used the axiological method, system analysis and synthesis, and content analysis. General philosophical methods were used to analyze chatbots - analysis, syn- thesis, generalization, logical and historical analysis. Results. The key aspects of chatbot development primarily involve understanding users’ needs and motivations. Such conversational user interfaces for accessing data and services represent a significant shift in how designers and developers traditionally approach interaction and user require- ments. Conclusions. Chatbots are altering user behavior as well as their needs. While chatbots can be beneficial for individuals with mental health issues, they also introduce certain risks and challenges. Ethical concerns primarily relate to the availability of a solid evidence base, the proper use of the technology, and data security.